Effectiveness of online advanced C.A.R.E suicide prevention gatekeeper training program among healthcare lecturers and workers in national university of Malaysia: A pilot study - Roslan, Amran Fadzrul; Pheh, Kai Shuen; Mahadevan, Raynuha; Bujang, Siti Mariam; Subramaniam, Ponnusamy; Yahya, Hanieza Fadzlina; Chan, Lai Fong (Frontiers in Psychiatry, 2023)
Background Suicide is a major cause of death among adolescents and young adults, especially students. This is particularly true for healthcare students with a higher risk and more access to lethal means. Thus, it is vital for healthcare educators who have regular contact with these healthcare students to be trained as gatekeepers in preventing suicide. Evidence of the effectiveness of such gatekeeper training, mainly using an online module, is lacking predominantly in Malaysia. This study aims to investigate the effectiveness of an online gatekeeper suicide prevention training program that is conducted for healthcare lecturers. Methods A single-arm interventional pre-and post-pilot study was conducted on a sample of healthcare lecturers and workers who are involved in supervising healthcare students. A purposive sampling technique was used to recruit 50 healthcare educators in Malaysia. The program was conducted by trained facilitators and 31 participants completed a locally validated self-rated questionnaire to measure their self-efficacy and declarative knowledge in preventing suicide; immediately before and after the intervention. Results Significant improvement was seen in the overall outcome following the intervention, mostly in the self-efficacy domain. No significant improvement was seen in the domain of declarative knowledge possibly due to ceiling effects; an already high baseline knowledge about suicide among healthcare workers. This is an exception in a single item that assesses a common misperception in assessing suicide risk where significant improvement was seen following the program. Conclusion The online Advanced C.A.R.E. Suicide Prevention Gatekeeper Training Program is promising in the short-term overall improvement in suicide prevention, primarily in self-efficacy.